Chronic Pancreatitis : From Basic Research to Clinical Treatment - Li, Zhao-Shen; Liao, Zhuan; Chen, Jian-Min; Férec, Claude (Springer Singapore : Imprint: Springer, 2017)
This book is a concise guide to the clinical diagnosis and management of chronic pancreatitis, presenting the latest research into the disease. It focuses on pathogenesis, epidemiology, genetics, diagnosis, endoscopic and surgical treatment, and prognosis. It also offers comprehensive descriptions of 4 diagnostic methods and discusses the contemporary management of chronic pancreatitis, including conservative, ESWL, interventional and surgical treatments. The final chapter includes 6 typical case presentations, which taken together provide a standard description of this condition.
Keywords: Medicine.; Gastroenterology.; elektronické knihy; electronic books